Note on Composition of Sapindus mukorossi Kernel Cake - Karnik, M. G.; Sharma, O. P.; Kukrettee, S. P. (Indian Forester, 1970)
The seed cake left after the extraction of oil from the kernels of Sapindus, ukorossi Gaertn. (soap nut) has been analysed. The cake is found to be rich in Nicrogen content. Qualitative tests indicated the presence of alkaloids and starch in the cake. The teste for tannins and sugars were negative. The results of the analysis are presented in the note.